Enhancing Self-Competence: Developing Inclusive Outdoor Learning Media for Children with Special Needs at Sekolah Alam Catur Cendikia - Yeni Latipah; Fajrin Mubarokah Parhani; Fitri Hidayah Sundawati; Dede Sujana; Fadhilah Dian Utami (Research Collaboration Community (Rescollacom), 2026)
Outdoor learning has potentials to support children’s motor, social, and self-confidence development, including children with special needs. However, its implementation in inclusive schools remains limited due to the lack of safe and adaptive learning media. This community engagement initiative aimed to develop inclusive outdoor learning media in the form of a mini wall climbing facility at Sekolah Alam Catur Cendikia, Bandung Regency. It also sought to enhance teachers’ capacity to utilize the media effectively in learning activities. The implementation was carried out through four stages including preparation, media construction, socialization and trial use, and evaluation, through a participatory approach involving lecturers, community service (KKN) students, teachers, and school stakeholders. Program evaluation was conducted using user satisfaction surveys, media feasibility assessment forms, observations, and interviews. The results indicated that the developed media was perceived as attractive, inclusive, and beneficial in promoting student engagement, more meaningful learning experiences, and social interaction. Although limitations were identified in terms of additional safety equipment, this program still provides a practical reference for inclusive schools in developing outdoor learning media to optimize learning environments and support the contextual implementation of activity-based outdoor learning.